42nd Street [videorecording (DVD)] - Bacon, Lloyd, 1890-1955; James, Rian, 1899-1953; Seymour, James; Berkeley, Busby, 1895-1976; Keeler, Ruby; Powell, Dick, 1904-1963; Baxter, Warner, 1889-1951; Daniels, Bebe, 1901-1971; Brent, George, 1904-1979; Rogers, Ginger, 1911-1995; Ropes, Bradford (Turner Entertainment : Warner Home Video, 2000)
A Broadway musical director has troubles during rehearsal, promotes the understudy and has a successful opening night. Chiefly memorable for the incredible musical numbers.